The effectiveness of think pair share (tps) method on reading narrative text - Salamun Salamun (Language-Edu, 2020)
Reading is one of the basic in English skills, just as important as writing, speaking, and listening. Besides, reading is closely related with other subject. There are many types in reading, one of them is narrative text. Narrative text is taught to the 2nd grade students of Junior High School. Students need some method in teaching narrative text that can help them to learn easier, one of the method that can be applied in teaching narrative text is Think Pair Share (TPS).  TPS is categorized as cooperative learning that demand students to share their ideas to their pair. The students worked in pair or in small group discussion to discuss the topic given and share each other. The objective of the research to know the effectiveness of Think Pair Share (TPS) method on students reading achievement.  The research design of this study is experimental research. The researcher apply quasi experimental. The subject of the research was second class students of MTs Mamba’us Sholihin Suci Manyar Gresik Tehnique of data collection is test, pre-test, treatment, and pos-test. Meanwhile, tehnique of data analysis , the researcher used IBM SPSS statistic 20 for windows. The result of the research showed that the significant value of students test both experimental group and control group was 0.00. It was lower than <0.05 as level of significant which meant that students who were taught by Think Pair Share methods get higher score of reading comprehension than the students who were taught by conventional method with the significant value of 0.00<0.05. So, this research showed that Think Pair Share method affect significantly on students’ reading comprehension of 2nd grade students of MTs Mamba’us Sholihin Suci ManyarGresik.  The result of this research, conclude that students who are taught by Think Pair Share method got higher score on their students reading comprehension.